Standar Proses dan Inovasi Pembelajaran Geografi dalam Kurikulum 2013 Sebagai Salah Satu Dasar Menjadikan Anak Bangsa yang Bermartabat - Rahmayoni Rahmayoni; Syafwi Anwar; Nola Aprilia Sukhaimi; Khairani Khairani (Departement of Mathematics Education, 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. Characteristics of objects of geographic study there are concrete and some are in the form of